(3GdadGMI GdQhejIs - (3bSWhS Hf GSchO GScjfIs ((3GHh GdfUQ gHI Gddg Hf jMji Hf gHI Gddg Hf LHQjd Hf fWjfG GdfUQGfi s)
(3ChdgG (B:s
(3cJGH bSWhS Hf GSchQG Scg YGde GdQhe hajgG hUa eGdG jSJZfi s
(3BNQgG (B:s
(3Je cJGH GdadGMjf s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B189 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdRQGYI h GdCYTGHs